Strategie di semplificazione testuale e di scrittura cooperativa tra studenti con retroterra migratorio e nativi - Gianluca Baldo (MediAzioni)
In recent years, the simplification and adaptation of texts have become more common strategies used to promote the inclusion and social participation of speakers with a migrant background. In schools, these experiences aim to stimulate a more active participation of whole student groups, often by introducing cooperative learning strategies, which have proven to be quite effective in bridging different codes and cultures as well. Another method used to incorporate the languages and dialects of origin of each student is the planning and writing of identity texts. These are short, personal compositions capable of shedding new light on the cultural background of young plurilingual authors. Within this reference framework, the linguistic experience of the Impact FVG 2014-2020 project took place. During the school year 2021-2022, a small number of sample groups of students from secondary schools in Friuli Venezia Giulia were involved in an experience of writing and raising awareness about the communicative resources present in the repertoires of emerging plurilingual groups and individuals.